16+3s-2s=24+24-20

Simple and best practice solution for 16+3s-2s=24+24-20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16+3s-2s=24+24-20 equation:


Simplifying
16 + 3s + -2s = 24 + 24 + -20

Combine like terms: 3s + -2s = 1s
16 + 1s = 24 + 24 + -20

Combine like terms: 24 + 24 = 48
16 + 1s = 48 + -20

Combine like terms: 48 + -20 = 28
16 + 1s = 28

Solving
16 + 1s = 28

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-16' to each side of the equation.
16 + -16 + 1s = 28 + -16

Combine like terms: 16 + -16 = 0
0 + 1s = 28 + -16
1s = 28 + -16

Combine like terms: 28 + -16 = 12
1s = 12

Divide each side by '1'.
s = 12

Simplifying
s = 12

See similar equations:

| 5-8(4x-4)=-7 | | 3(x+2)=6(x-1)+6 | | -16=y-13 | | 60-.04x=80 | | 3/10-(-2/3) | | -3=z-18 | | 30+3*x-2*(12-x)=38 | | 10-2m=m+4 | | 8y-7=14y+23 | | 4x+12=38 | | -6x^2=-35 | | 10/62 | | 9x-7=6x+38 | | 50=x-15 | | 27x+901= | | 8x-3=5x-57 | | n/4-5=17 | | 5(x+6)-(x+28)=-2x | | f(x)=x-9/X^2-16 | | 8x+2=6x+36 | | 8(3x-4)=14x-2 | | 17x-9x=24 | | 5x-(2x+9)=9 | | -97x+42x= | | 6(7x-6)=27 | | 15-6x=-51 | | c+1.7=2.6 | | 96-3x=8 | | -6i+4= | | 6x-17=-107 | | 5(x-6)-(x+28)=-2x | | (x-3+5i)(x-3-5i)=0 |

Equations solver categories